The Moralizing Effect: self-directed emotions and their impact on culpability attributions - Sirgiovanni, Elisabetta; Smolenski, Joanna; Abelson, Ben; Webb, Taylor (Frontiers in Integrative Neuroscience, 2023)
A general trend in the psychological literature suggests that guilt contributes to morality more than shame does. Unlike shame-prone individuals, guilt-prone individuals internalize the causality of negative events, attribute responsibility in the first person, and engage in responsible behavior. However, it is not known how guilt-and shame-proneness interact with the attribution of responsibility to others. In two Web-based experiments participants reported their attributions of moral culpability (i.e., responsibility, causality, punishment and decision-making) about morally ambiguous acts of killing in different conditions. In Study 1 the vignettes were presented in the 1st person, while in Study 2 in the 3rd person. To test proneness to guilt and shame, we utilized the GASP scale, which differentiates between the affective and behavioral components of each emotion. We found that guilt-and shame-proneness were associated with the severity of attributions in both the first and the third person, but the effect was strong only in the guilt case (both subtypes) and shame-affect case, and not in the shame-behavior case. We name this the Moralizing Effect.We wonder whether our finding that guilt-prone people tend to attribute a higher degree of culpability to others is really consistent with the view that guilt motivates people to choose the "moral paths in life". . This echoes views about harmful aspects of guilt, which have been expressed historically in philosophy, for example, by Friedrich Nietzsche.